SEASONAL PATTERNS OF INFECTION BY Kudoa sp. (MYXOZOA) IN THE CATFISHES IN THE BRAZILIAN AMAZON REGION - João Lauro Figueiredo dos Santos; Jacqueline Pompeu Abrunhosa; José Ledamir Sindeaux-Neto; Elideth Pacheco Monteiro; Edilson Rodrigues Matos (Boletim do Instituto de Pesca)
The myxosporidians of the genus Kudoa cause post mortem myoliquefaction in fishery products and may potentially transmit zoonoses. The present study describes the infection of the skeletal musculature by Kudoa sp. in two sea catfish species, Cathorops spixii (Agassiz, 1829) and Cathorops agassizii (Eigenmann & Eigenmann, 1888), captured monthly in an estuary of the municipality of Vigia de Nazaré, in Pará, northern Brazil between March, 2015, and August, 2016. The morphological features of the spores are described, and the influence of the seasonal variation on the occurrence of the parasite is discussed. The specimens were taken to the laboratory for analysis using a hand lens and light microscopy. When parasites were identified in the musculature, small fragments of the tissue were removed for histological processing and staining by the Hematoxylin-Eosin, Ziehl-Neelsen, May Grunwald-Giemsa, and Gomori techniques. The pseudocysts were found in the muscle fibers, and the spores were star-shaped with elongated extremities and 4 piriform/rounded polar capsules of equal size. No infections were observed in the fish specimens collected during the rainy season, whereas all (100%) of the Cathorops specimens examined during the dry season were infected. This indicates that the ecology and infection patterns of the parasite (identified as a species of the genus Kudoa, on the basis of its morphological features) is influenced by salinity levels.